Current Imbalance in Parallel Battery Strings Measured Using a Hall‐Effect Sensor Array. Issue 4 (26th February 2021) - Luca, Robert; Whiteley, Michael; Neville, Toby; Tranter, Tom; Weaving, Julia; Marco, James; Shearing, Paul R.; Brett, Dan J. L.
Abstract : Herein, individual cell currents in parallel connected battery strings are measured using micro‐Hall‐effect sensors. Cells are routinely connected in electrical series and parallel to meet the power and energy requirements of automotive and consumer electronics applications. Cells connected in series have been extensively studied; however, cells in parallel are often assumed to be a "black box" in battery management systems. Poor pack design can result in positive feedback between current and temperature differentials along the parallel string, driving greater levels of heterogeneous behavior and uneven degradation. Herein, a noninvasive multisensor array board using Hall‐effect sensors is used to individually record the current passing through eight parallel connected cells in two different electrical configurations, showing highly heterogeneous current distribution. Characteristic "waves" of current and temperature are found to propagate along the parallel battery string and cell rebalancing is found to occur over hundreds of seconds with individual cell currents of up to 1 C rate. Abstract : Current heterogeneities in parallel battery strings may result in accelerated and imbalanced degradation of cells within vehicle battery packs. Herein, a measurement technique using micro‐Hall‐effect sensors, small enough to be integrated into module casings, is presented for an on‐board measurement and diagnostic solution for automotive battery packs. This is demonstrated on an 8p1s 18650 module.